Carbon nanotubes as catalysts for wet peroxide oxidation: the effect of surface chemistry - Martin-Martinez, Maria (2020)
Three magnetic carbon nanotube (CNT) samples, named A30 (N-doped), E30 (undoped) and E10A20 (selectively N-doped), synthesized by catalytic chemical vapor deposition, were modified by introducing oxygenated surface groups (oxidation with HNO3, samples CNT-N), and by heat treatment at 800 °C for the removal of surface functionalities (samples CNT-HT). Both treatments lead to higher specific surface areas. The acid treatment results in more acidic surfaces, with higher amounts of oxygenated species being introduced on Ndoped surfaces. Heat-treated samples are less hydrophilic than those treated with nitric acid, heat treatment leading to neutral or basic surfaces, only N-quaternary and N-pyridinic species being found by XPS on N-doped surfaces. These materials were tested in the catalytic wet peroxide oxidation (CWPO) of highly concentrated 4-nitrophenol solutions (4-NP, 5 g L−1) at atmospheric pressure, T=50 °C and pH=3, using a catalyst load of 2.5 g L−1 and the stoichiometric amount of H2O2 needed for the complete mineralization of 4-NP. The high temperature treatment enhanced significantly the activity of the CNTs towards CWPO, evaluated in terms of 4-NP and total organic carbon conversion, due to the increased hydrophobicity of their surface. In particular, E30HT and E10A20HT were able to remove ca. 100% of 4-NP after 8 h of operation. On the other hand, by treating the CNTs with HNO3, the activity of the less hydrophilic samples decreased upon increasing the concentration of surface oxygen-containing functionalities, whilst the reactivity generated inside the opened nanotubes improved the activity of the highly hydrophilic A30 N.